Complications of COVID-19 infection in pregnant women: Protocol of a scoping review (Research, Society and Development, 2022)
Objective: To map and analyze the scientific production on the complications of COVID-19 infection in previously healthy pregnant women. Method: A scoping review will be carried out, guided by the recommendations of the Joanna Briggs Institute and the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) instrument, and by the research question: What are the complications of COVID-19 infection in previously healthy pregnant women, reported in the scientific literature? built with the PCC strategy, with: P (Person): Previously healthy pregnant women with COVID-19 infection; C (Concept): Complications of infection in the health of pregnant women, and C (Context): International scientific literature, in this case involving all scenarios of health care for pregnant women. The inclusion criteria were constituted in order to demonstrate the amplitude of the phenomenon, and the exclusion criteria in order to avoid possible biases due to confounding variables. The search strategy will be formulated based on DECS and MESH descriptors, in the following databases: PubMed Central, EMBASE indexing, Scopus, Virtual Health Library (BVS) and Scientific Electronic Library online (SCIELO). The steps of reading titles, abstracts, full text will be followed, with data extraction being done through a collection instrument. The data will be organized in Flow diagram, graphs and tables, using simple and absolute frequency and narrative analysis. The study will be carried out from March to November 2022.